Contemporary Europe - Sakwa, Richard; Stevens, Anne 1942- (New York Palgrave Macmillan, 2012)
"This fully revised third edition provides a wide-ranging introduction to political, economic and social life across the whole continent. Ideal for students new to the subject, this popular text stimulates fresh thinking on issues and debates"--Provided by publisher.
Preface -- Introduction: The Many Dimensions of Europe -- Historical Background -- Towards One Europe? -- The European Union: The Challenge of Success -- Government and Politics -- Political Participation in Europe -- Social Structure -- The European Economy -- Regions and Regional Politics in Europe -- European Security -- The Cultural Dimension -- Conclusion.
Keywords: Europe -- Politics and government -- 1989-.; Europe -- Politics and government -- 20th century